Retrospective Analysis of the Impact of SARS-CoV-2 (COVID-19) on Pregnancy and Neonatal Outcomes - Leyla Sero; Nilufer Okur; Duygu Tunçel; Mehmet Nur Talay; Mustafa Fırat Aydın; Suleyman Cemil Oglak (Wiley, 2024)
Conclusion: While COVID-19 infection in pregnancy seriously affects mortality and morbidity in pregnant women, it also causes mortality and morbidity on the fetus.